Food web reconstruction through phylogenetic transfer of low‐rank network representation. Issue 12 (30th March 2022) - Strydom, Tanya; Bouskila, Salomé; Banville, Francis; Barros, Ceres; Caron, Dominique; Farrell, Maxwell J.; Fortin, Marie‐Josée; Hemming, Victoria; Mercier, Benjamin; Pollock, Laura J.; Runghen, Rogini; Dalla Riva, Giulio V.; et al.
Abstract: Despite their importance in many ecological processes, collecting data and information on ecological interactions is an exceedingly challenging task. For this reason, large parts of the world have a data deficit when it comes to species interactions and how the resulting networks are structured. As data collection alone is unlikely to be sufficient, community ecologists must adopt predictive methods. We present a methodological framework that uses graph embedding and transfer learning to assemble a predicted list of trophic interactions of a species pool for which their interactions are unknown. Specifically, we 'learn' the information (latent traits) of species from a known interaction network and infer the latent traits of another species pool for which we have no a priori interaction data based on their phylogenetic relatedness to species from the known network. The latent traits can then be used to predict interactions and construct an interaction network. Here we assembled a metaweb for Canadian mammals derived from interactions in the European food web, despite only 4% of common species being shared between the two locations. The results of the predictive model are compared against databases of recorded pairwise interactions, showing that we correctly recover 91% of known interactions. The framework itself is robust even when the known network is incomplete or contains spurious interactions making it an ideal candidate as a tool for filling gaps when it comes to species interactions. We provide guidance on how this framework can be adapted by substituting some approaches or predictors in order to make it more generally applicable. Résume: Malgré leur importance dans de nombreux processus écologiques, la collecte de données et d'informations sur les interactions écologiques est une tâche extrêmement complexe. Pour cette raison, de nombreuses régions du monde révèlent un déficit de données en ce qui concerne les interactions entre les espèces et la structure des réseaux qui en résultent. Comme il est peu probable que la collecte de données soit suffisante à elle seule, les écologistes des communautés doivent adopter des méthodes prédictives. Nous présentons un cadre méthodologique qui utilise l'incorporation graphique et l'apprentissage par transfert pour établir une liste prédictive des interactions trophiques d'un bassin d'espèces dont les interactions sont inconnues. Plus précisément, nous « apprenons » l'information (caractères latents) des espèces à partir d'un réseau d'interaction connu et inférons les caractères latents d'un autre bassin d'espèces pour lequel nous n'avons pas de données d'interaction a priori fondées sur leur lien phylogénétique avec les espèces du réseau connu. Les traits latents peuvent ensuite être utilisés pour prédire les interactions et construire un réseau d'interaction. Ici, nous avons assemblé un méta‐réseau (metaweb) pour les mammifères canadiens à partir des interactions dans le réseau trophique européen, en dépit d'un partage d'espèces communes de seulement 4% entre les deux sites. Les résultats du modèle prédictif sont comparés aux bases de données répertoriées d'interactions par paires, montrant que nous recouvrons correctement 91% des interactions connues. Le cadre est intrinsèquement robuste, même lorsque le réseau connu est incomplet ou contient des interactions fallacieuses, en faisant un candidat idéal comme outil pour combler les lacunes en ce qui concerne les interactions entre les espèces. Nous fournissons des conseils sur la façon dont ce cadre peut être adapté en remplaçant certaines approches ou certains prédicteurs afin de le rendre plus généralement applicable.